Sebaran Konsentrasi Coliform Dan Escherichia Coli Pada Air Tanah Dangkal Kota Gorontalo - Marike Mahmud (Jambura Geoscience Review, 2021)
This study aims to analyze the spatial distribution of coliform and E. coli in groundwater Gorontalo City and the factors that influence it. The sampling locations were taken from 9 sub-districts consisting of 27 villages. The nine sub-districts consist of Dumbo Raya, Hulondalangi Kota Barat, Kota Utara, Kota Timur, Kota Selatan, Sipatana, Dungingi, and Padebuolo Districts. Sampling in each village consisted of 1 sample and was taken randomly. Kota Utara Sub-district consisted of 1 sample location, namely Dembe Jaya Village. Kota Timur Sub-district consists of 2 villages, namely Padebuolo and Heledulaan Selatan villages. Kota Selatan sub-district consists of Limba U 1. Kota Tengah sub-district consists of Liluwo Village. The Sipatana sub-district consists of Tanggikiki, Bulotadaa, and Tapa Villages. Dungingi sub-district consists of Tulandenggi and Libuo Villages. The total number of samples was 27. The analysis was carried out at the Gorontalo District Health Office, UPTD of Water Quality Laboratory Installation. The sampling method was carried out aseptically. Measurements in the laboratory used the MPN method. The quality standard that became the reference was Permenkes (Health Minister Regulation) number 32 of 2017 Annex 1 regarding water for sanitation and hygiene. The results of the analysis showed that the distribution of the number of coliform bacteria, in general, was at the quality standard set. A total of 24 villages of 27 locations were above the established quality standard. Regarding the number of E. coli bacteria from 27 locations, there were 5 locations above the established quality standards. The factor that affected the pollution was the distance of the septic tank which was very close to the well (water source).